Inhibition of Fatty Acid Synthase Upregulates Expression of CD36 to Sustain Proliferation of Colorectal Cancer Cells - Drury, James; Rychahou, Piotr G.; He, Daheng; Jafari, Naser; Wang, Chi; Lee, Eun Y.; Weiss, Heidi L.; Evers, Bernard Mark; Zaytseva, Yekaterina Y. (Frontiers in Oncology, 2020)
Fatty acid synthase, a key enzyme of de novo lipogenesis, is an attractive therapeutic target in cancer. The novel fatty acid synthase inhibitor, TVB-3664, shows anti-cancer activity in multiple cancers including colorectal cancer; however, it is unclear whether uptake of exogeneous fatty acids can compensate for the effect of fatty acid synthase inhibition. This study demonstrates that inhibition of fatty acid synthase selectively upregulates fatty acid translocase (CD36), a fatty acid transporter, in multiple colorectal cancer models including colorectal cancer cells with shRNA mediated knockdown of fatty acid synthase and genetically modified mouse tissues with heterozygous and homozygous deletion of fatty acid synthase. Furthermore, human colorectal cancer tissues treated with TVB-3664 show a significant and selective upregulation of CD36 mRNA. shRNA-mediated knockdown of CD36 and inhibition of CD36 via sulfosuccinimidyl oleate, a chemical inhibitor of CD36, decreased cell proliferation in vitro and reduced tumor growth in subcutaneous xenograft models. Isogenic cell populations established from patient derived xenografts and expressing high levels of CD36 show a significantly increased ability to grow tumors in vivo. The tumor-promoting effect of CD36 is associated with an increase in the levels of pAkt and survivin. Importantly, combinatorial treatment of primary and established colorectal cancer cells with TVB-3664 and sulfosuccinimidyl oleate shows a synergistic effect on cell proliferation. In summary, our study demonstrates that upregulation of CD36 expression is a potential compensatory mechanism for fatty acid synthase inhibition and that inhibition of CD36 can improve the efficacy of fatty acid synthase-targeted therapy.